Phobos and Deimos polarimetric observations interpreted through analogue measurements - Jeremie Lasue; Edith Hadamcik; Jean-Baptiste Renard; Olivier Poch; Pierre Beck (2025)
Introduction:The Martian Moon eXploration (MMX) Japanese mission is scheduled to be launched in 2026 to explore the martian moons system. The mission will orbit and land on Phobos, observe Deimos and retrieve and return more than 10 grams of regolith from the surface of Phobos back to Earth by 2031 [1, 2]. The scientific goals of the mission are to better understand the formation and evolution of the martian moons, to decipher their origin, and observe the surface and atmosphere of Mars from a different vantage point.The origin of Phobos and Deimos, whether as asteroids by capture, or fragments of Mars by impacts, remains debated in the community (see [3] and references therein). The peculiar dynamics of their orbits seems consistent with an origin from impacts. However, their infrared spectra are most consistent with primitive asteroids with a low albedo, red slope and few if any mineralogical absorption features [4].Method: Polarimetric observations are a useful tool to classify and decipher the evolution of planetary surfaces [5] and has been especially used to study the properties of asteroid families [6]. Few observations in polarization have been made in the 1970s of Phobos and Deimos by the Mariner 9 space mission and ground-based observations [7, 8]. At large phase angles from 74 to 81 degrees, those observations were done in the visible at 570 nm, while low phase angle observations below about 30 degrees were done in the ultraviolet at 233 nm. We can directly compare those measured values to the ones observed for different types of asteroids from the ground in the U and V astronomical filters [9, 10] as shown in Figure 1.Then the PROGRA2 experiment is a polarimetric goniometer that studied the light-scattering properties of dust particles of various size distributions under Earth’s gravity either deposited or lifted by an air-draught, as well as levitated under microgravity conditions in dedicated flight campaigns. The experiment was used to study the polarimetric behavior of various astronomical analogues including crushed meteorite samples that were levitated or deposited [11]. These meteorites included: Allegan, an H5 ordinary chondrite analogue to S-type asteroids, Allende, a CV3 primitive carbonaceous chondrite analogue to C-, L- or K-type asteroids (crushed in two different grain sizes: fine sieved